A COMPARISON OF OBSERVATION WITH MODELING FOR ALBEDO AND TRANSMITTANCE OF SNOW - アオキ, テルオ; セコ, カツモト; アオキ, タダオ; フカボリ, マサシ; AOKI, Teruo; SEKO, Katsumoto; AOKI, Tadao; FUKABORI, Masashi (National Institute of Polar Research, 1994)
P(論文) Snow surface albedo and transmittance inside the snow have been investigated by observation and modeling. Observations were taken by a grating type spectrometer at Tokamachi in March 1993. The observed snow was old and very wet. Microscope photo-graphs of snow grains taken at this time indicate that snow grain is spherical particles with size of about 1.0μm. Surface albedo and transmittance of snow by a multiple scattering model for the atmosphere-snow system with pure snow grain size of 1.0μm have similar wavelength dependence to our observation. Though both the maximum albedo and transmit-tance have been observed at the wavelength 0.55μm, model calculation shows that this wavelength is 0.45μm. Moreover, the observed albedo is lower than the model with a maximum of 10% in visible region. It is considered that these differences are mainly due to impurities and/or liquid water in natural snow. departmental bulletin paper